A factor analytic study of the suki relationship in selected small eateries in Antipolo, Marikina and Taytay - Adornado, Heddy Pamintuan (College of Home Economics, University of the Philippines, 2015)
Customer loyalty is a well-known concept that has been studied for years. It has been linked to customer satisfaction and profitability. Due to intense competition, food service establishments are continuously creating customer loyalty programs just to retain their customers and prevent them from transferring to other competitors. Western literature on customer loyalty are numerous. However, few literature in the Philippines exist regarding customer loyalty. One of them is the suki relationship that has been cited by authors who visited the country. This study aims to define the suki and the suki relationship and uncover the factors that contribute to the relationship. Survey questionnaires were distributed to 225 customer-respondents and 75 seller-respondents from 15 local eateries in Antipolo, Marikina, and Taytay. Statistical methods of factor analysis and ANOVA were applied to the data gathered. The research results show the confirmation on both the customer and the seller of the existence of the suki relationship. The definition of suki is no longer limited to being loyal (tapat). It now includes traits of being pleasant (kaaya-aya), and good (mabuti). The underlying factors that contributed to its existence are reciprocity, trustworthiness, and pakikisama, which were considered relevant by both parties. However, the comparison of factor outcomes for both the seller and the customer yielded differences in perception among the three study locales on certain factors. Further confirmatory studies on the suki relationship and its factors are still needed. Local and government support is likewise encouraged because of the growing local eatery industry.